2008
DOI: 10.1071/ar07185
|View full text |Cite
|
Sign up to set email alerts
|

The influences of genotype, environment, and genotype×environment interaction on wheat quality

Abstract: Knowledge of the relative contributions of genotype (G), environment (E), and genotype and environment interaction (G × E) effects on wheat (Triticum aestivum L.) quality leads to more effective selection in breeding programs and segregation of more uniform parcels of grain better suited to the needs of customers. Their effects on wheat quality were reviewed using papers obtained from 4 major international databases. The literature is dominated by research from North America, with lesser contributions from Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 98 publications
13
57
0
Order By: Relevance
“…However, based on such trials, breeders have chosen the best lines to develop as cultivars. Williams et al (2008) showed that experiments assessing wheat quality characteristics were most often conducted in two years (above 35%) or in one year (above 15%); multi-year trials are rare because they are costly and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on such trials, breeders have chosen the best lines to develop as cultivars. Williams et al (2008) showed that experiments assessing wheat quality characteristics were most often conducted in two years (above 35%) or in one year (above 15%); multi-year trials are rare because they are costly and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The variation of the quality indices when growing each individual variety under different environments is always helpful both for the distribution of the new varieties and for their improvement in breeding programs (Gomez-Becera et al, 2010). The data on the variation of winter wheat quality is contradictable with regard to the level of genotype effect (Gomez-Beccera et al, 2010;Williams et al, 2008). In breeding there is always the question whether the high quality of a given variety under favorable environments is a prerequisite for the realization of its high-quality potential under unfavorable environments, too, or is it and impediment for its stability (Hristov et al, 2010;Tsenov et al, 2004).…”
Section: Evaluation Of Genotype Environment and Their Interaction Fomentioning
confidence: 99%
“…The exception was wet gluten content, which was affected most by the interaction location x year. Hristov et al (2010), Mladenov et al (2001), Williams et al (2008) have found out that in spite of the significant effect of the interaction genotype x environment on the expression of the quality parameters of wheat, this effect was less significant than the independent influences of the genotype and the location. Table 4.…”
Section: Evaluation Of Genotype Environment and Their Interaction Fomentioning
confidence: 99%
See 2 more Smart Citations